Prevention of Surgical Site Infection in Spine Surgery. Issue 3 (21st February 2017) - Anderson, Paul A.; Savage, Jason W.; Vaccaro, Alexander R.; Radcliff, Kristen; Arnold, Paul M.; Lawrence, Brandon D.; Shamji, Mohammed F.
Abstract: BACKGROUND: Spine surgery is complicated by an incidence of 1% to 9% of surgical site infection (SSI). The most common organisms are gram-positive bacteria and are endogenous, that is are brought to the hospital by the patient. Efforts to improve safety have been focused on reducing SSI using a bundle approach. The bundle approach applies many quality improvement efforts and has been shown to reduce SSI in other surgical procedures. OBJECTIVE: To provide a narrative review of practical solutions to reduce SSI in spine surgery. METHODS: Literature review and synthesis to identify methods that can be used to prevent SSI. RESULTS: SSI prevention starts with proper patient selection and optimization of medical conditions, particularly reducing smoking and glycemic control. Screening for staphylococcus organisms and subsequent decolonization is a promising method to reduce endogenous bacterial burden. Preoperative warming of patients and timely administration of antibiotics are critical to prevent SSI. Skin preparation using chlorhexidine and alcohol solutions are recommended. Meticulous surgical technique and maintenance of sterile techniques should always be performed. Postoperatively, traditional methods of tissue oxygenation and glycemic control remain essential. Newer wound care methods such as silver impregnation dressing and wound-assisted vacuum dressing are encouraging but need further investigation. CONCLUSION: Significant reduction of SSIs is possible, but requires a systems approach involving all stakeholders. There are many simple and low-cost components that can be adjusted to reduce SSIs. Systematic efforts including understanding of pathophysiology, prevention strategies, and system-wide quality improvement programs demonstrate significant reduction of SSI.